The Theory of Strong Position: Navigating Success in a Dynamic World (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article delves into the profound concept of the Theory of Strong  Position, a guiding philosophy that transcends the boundaries of diverse domains—from  professional pursuits to personal relationships. Through a metaphorical lens of  navigating turbulent waters, the piece explores how this theory provides individuals and  entities with a strategic roadmap for not just weathering life's storms but harnessing their  energy for growth. The article concludes with a poignant reflection on adaptability and  seizing opportunities—a fitting closure to a narrative that encourages readers to embrace  the fluidity of life and secure positions that stand resilient against the test of time